Motives, frequency and attitudes toward emoji and emoticon use. Issue 7 (October 2018) - Prada, Marília; Rodrigues, David L.; Garrido, Margarida V.; Lopes, Diniz; Cavalheiro, Bernardo; Gaspar, Rui
Highlights: Participants reported using emoji more often than emoticons. Participants reported more positive attitudes and more motives for using emoji. Women reported using emoji more often and more positive attitudes. Younger participants use more and have more positive attitudes toward both cues. Gender differences in emoji use were particularly evident in younger participants. Abstract: Electronic Mediated Communication (EMC) has become highly prevalent in our daily lives. Many of the communication formats used in EMC are text-based (e.g., instant messaging), and users often include visual paralinguistic cues in their messages. In the current study, we examined the usage of two such cues – emoji and emoticons. Specifically, we compared self-reported frequency of use, as well as attitudes (6 bipolar items, e.g., "fun" vs. "boring") and motives for their usage (9 motives, e.g., "express how I feel to others"). We also examined these indicators according to age and gender. Overall, participants ( N = 474, 72.6% women; M age = 30.71, SD = 12.58) reported using emoji (vs. emoticons) more often, revealed more positive attitudes toward emoji usage, and identified more with motives to use them. Moreover, all the ratings were higher among younger (vs. older) participants. Results also showed that women reported to use emoji (but not emoticons) more often and expressed more positive attitudes toward their usage than men. However, these gender differences were particularly evident for younger participants. No gender differences were found for emoticons usage. These findings add to the emerging body of literature by showing the relevance of considering age and gender, and their interplay, when examining patterns of emoji and emoticons use.